ANALYSIS EFFICIENCY AND EFFECTIVENESS SHOPPING INFRASTRUCTURE MSMEs THROUGH IMPLEMENTATION OF REGULATIONS PRESIDENT NUMBER 12 YEAR 2021 : STUDY CASE FUND MEMBER POKIR DPRD CITY TIDORE NORTH MALUKU - Runtunuwu, Prince Charles Heston; Rajasekera, Jay (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2023)
The aims of this s study to analyze Development MSME infrastructure through Implementation Regulation President Number 12 of 2021. This Approach Study, is Descriptive Qualitative: Data source: Secretary of Tidore City Islands area, Head of ULP Tidore Islands, Chief Field Cooperative Department of Industry, Trade and Cooperatives . Planning for MSME development in Tidore City Island is not yet appropriate and not unidirectional with Regulation President Number 12 Year 2021. For that, Tidore City Government Island needs To do socialization related with development suitable MSME infrastructure with Regulations President number 12 of 2021 so that need existence planned coordination Among Tidore City government and related stakeholders so that so that planning MSME development can be done with get support budget.